Предмет: Алгебра,
автор: texr
упростите выражение (C+4)(C-4)(C^2+16)-(C^2-8)^2
Ответы
Автор ответа:
2
( c + 4 )( c - 4 )( c^2 + 16 ) = ( c^2 - 16 )( c^2 + 16 ) = c^4 - 256
- ( c^2 - 8 )^2 = - ( c^4 - 16c^2 + 64 ) = - c^4 + 16c^2 - 64
c^4 - 256 - c^4 + 16c^2 - 64 = 16c^2 - 320
c = - 1/4
c^2 = 1/16
16 * ( 1/16 ) - 320 = 1 - 320 = - 319
Автор ответа:
1
(С^2-16)(С^2+16)-(С^2-8)^2=C^2-256-C^4+16C^2-64=17C^2-C^4-320
Похожие вопросы
Предмет: Английский язык,
автор: gribtana707
Предмет: Английский язык,
автор: grigoryancyuzanna35
Предмет: Химия,
автор: aglalyka
Предмет: Математика,
автор: лика349
Предмет: Биология,
автор: prostoshkolnic